Hubungan Protein Urin dengan Berat Jenis Urin pada Pasien Nefropati Diabetik - Putri, Najwa Naraniya; Kurniati, Intanri; Yuningrum, Hesti; Susianti (Medula, 2024)
Diabetic nephropathy is one of the main causes of end-stage renal failure or End Stage Renal Disease (ESRD) in patients with type 2 diabetes. Diabetic nephropathy is defined as the presence of albumin or protein of more than 30 mg/day in urine on two examinations within a period of 3-6 months, as well as a decrease in the glomerular filtration rate. Urinalysis examination using the dipstick method is carried out for certain indications or suspicions of complications of diabetes mellitus, one of which is diabetic nephropathy. Dipstick examination can detect protein, pH, glucose, specific gravity, ketones, urobilinogen, nitrite, blood, bilirubin, and leukocyte esterase. The specific gravity of urine depends on the concentration of glucose, urea, and protein particles in the solution. Therefore, the purpose of this study was to determine the relationship between protein in urine and specific gravity in patients with diabetic nephropathy. Observational analytical research was conducted with a cross-sectional approach. This study was conducted at the Medical Records Installation of Dr. H. Abdul Moeloek Hospital. The population of this study was diabetic nephropathy patients treated at Dr. H. Abdul Moeloek Hospital in January-December 2023. The sampling technique used the total sampling technique so that 49 samples were obtained that met the inclusion and exclusion criteria. The data obtained were analyzed using the Spearman correlation test. The results showed a correlation coefficient (r) of 0.589 and a significance p-value = 0.000. There is a relationship between urine protein and urine specific gravity in diabetic nephropathy patients.